Analysis of Exergy Efficiency and Ways of Energy Saving in Air Conditioning System for a Cleanroom - Dmytro Harasym; Volodymyr Labay (Energy Engineering and Control Systems)
In modern technologies, which are related to energy transformation, namely in air conditioning systems, important places are occupied by equipment and processes, the objective estimation of value of its energy perfection can be defined only on the basis of analysis of its exergy efficiency. So, reducing the cost of energy consumed by air conditioning systems preconditions the need for its optimization, which can be fully achieved by virtue of exergy analysis that takes into account not only the quantity but also the quality of energy spent. Nowadays cost estimates can’t be the only measure of effectiveness of energy equipment that is using energy resources. Exergy is a physical not an economical criterion and defines its independence from conjectural fluctuations of prices. At the same time, cost parameters don’t allow making long term predicting. The minimum should be defined not by financial costs but exergy losses per unit of received heat. Unfitness of just the financial costs is obvious. Analysis of exergy efficiency of the central straight flow air conditioning system (ACS) for cleanroom, that was gained on its innovation mathematical research model depending on different factors, which have influence on its work was presented in this article, and the ways of energy saving for this ACS was proposed. It was found that temperature difference between inside and supplied air in a room, temperature of inside air which depends on temperature of outside air and coefficient of transformation EER of refrigerator machine of ACS have the biggest impact on exergetic output-input ration of chosen air conditioning system.